Use of microsatellite marker loss of heterozygosity in accurate diagnosis of pancreaticobiliary malignancy from brush cytology samples. Issue 12 (11th November 2004) - Khalid, A; Pal, R; Sasatomi, E; Swalsky, P; Slivka, A; Whitcomb, D; Finkelstein, S
Abstract : Background: Brush cytology of biliary strictures to diagnose pancreaticobiliary malignancy suffers from poor sensitivity. Aim: To improve the diagnostic yield of pancreaticobiliary brush cytology through analysis of tumour suppressor gene linked microsatellite marker loss of heterozygosity (LOH) and k-ras codon 12 mutation detection. Methods: Twenty six patients with biliary strictures underwent endoscopic retrograde cholangiography with brush cytology. A panel of 12 polymorphic microsatellite markers linked to six tumour suppressor genes was developed. Genomic DNA from cell clusters acquired from brush cytology specimens and microdissected surgical malignant and normal tissue underwent polymerase chain amplification reaction (PCR). PCR products were compared for LOH and k-ras codon 12 mutations. Results: Seventeen patients were confirmed to have pancreaticobiliary adenocarcinoma. Nine patients had benign strictures (eight proven surgically, one by follow up). Cytomorphological interpretation was positive for malignancy (n = 8), indeterminate (n = 10), and negative for malignancy (n = 8). Selected malignant appearing cytological cell clusters and microdissected histological samples from cancer showed abundant LOH characteristic of malignancy while brushings from nine cases without cancer carried no LOH (p<0.001). LOH and k-ras mutations profile of the cytological specimens was almost always concordant with the tissue samples. Presence of k-ras mutation predicted malignancy of pancreatic origin (p<0.001). Conclusion: LOH and k-ras codon 12 mutation analysis of PCR amplified DNA from biliary brush cytology discriminates reactive from malignant cells, with 100% sensitivity, specificity, and accuracy. Minor variations in LOH in brushings and in different sites within the same tumour likely reflect intratumoral mutational heterogeneity during clonal expansion of pre- and neoplastic lineages.